Burger's Medicinal Chemistry and Drug Discovery 2021
DOI: 10.1002/0471266949.bmc235.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery and Development for Kinetoplastid Diseases

Abstract: In this article, we review the disease, biology, and biochemistry of kinetoplastids, as well as the new drugs and drug candidates that have entered the clinic in the last decade. We also describe examples of the preclinical exploration of small molecules against various protein targets (e.g. cysteine proteases, the proteasome, and tubulin), as well as cutting‐edge molecular and computational strategies and technologies being brought to bear to discover and develop new antitrypanosomal drugs. For comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 325 publications
0
11
0
Order By: Relevance
“…Available treatments are suboptimal for both diseases. Benznidazole and Nifurtimox, the current chemotherapeutic options for CD, are only effective in the acute phase and are associated with significant adverse effects, which include gastric and neurological disorders [ 3 , 10 , 11 , 12 , 13 ]. Moreover, it was shown that chronic asymptomatic patients have no clinical benefit on their cardiac condition after Benznidazole therapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Available treatments are suboptimal for both diseases. Benznidazole and Nifurtimox, the current chemotherapeutic options for CD, are only effective in the acute phase and are associated with significant adverse effects, which include gastric and neurological disorders [ 3 , 10 , 11 , 12 , 13 ]. Moreover, it was shown that chronic asymptomatic patients have no clinical benefit on their cardiac condition after Benznidazole therapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a reduction in mortality and infections, mainly attributed to vector control and an overall improvement in socioeconomic conditions, Chagas disease is estimated to have caused 9490 deaths in 2019, mostly in Latin America . Currently, only two drugs are available for use against Chagas disease: Nifurtimox and Benznidazole, which are efficient mainly in the acute phase. After the progression of the disease to the indeterminate or chronic phases, no effective treatment is available. Furthermore, Nifurtimox and Benznidazole are associated with serious adverse side effects and long treatment duration (up to 2 months).…”
Section: Introductionmentioning
confidence: 99%
“…Two subspecies of Trypanosoma brucei elicit different Human African trypanosomiasis (HAT) patterns: Trypanosoma brucei gambiense causes a slowly progressing disease in western and central Africa, while Trypanosoma brucei rhodesiense induces a more rapid pathology in eastern and southern Africa. Although five drugs are used for HAT therapy, some have limited efficacy and suffer from drug resistance. Suramin and pentamidine are used to treat the first-stage disease caused by T. b. rhodesiense and T.…”
Section: Introductionmentioning
confidence: 99%
“…b. gambiense includes a combination of eflornithine and nifurtimox, whereas melarsoprol, which comes with a risk of severe adverse events, remains the only acceptable option for T. b. rhodesiense . Recently, fexinidazole was approved by the WHO for treatment of first and second stage infection by T.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation